How Is Building Sustainability Understood?—A Study of Research Papers and Sustainability Reports - Isaksson, Raine; Rosvall, Max; Espuny, Maximilian [UNESP]; Nunhes, Thais Vieira [UNESP]; de Oliveira, Otávio José [UNESP] (MDPI, 2022)
The global process of providing shelter plays an important role in sustainable development. Buildings are estimated to be responsible for up to 50% of global carbon emissions, which makes building a major issue for climate change. The common saying is that what “we cannot measure, we cannot improve”. This assumes that we know what to measure, which requires that we have a common understanding. The indication is that there could be problems in how we understand building sustainability, which, if true, will reduce change towards sustainable building. The purpose of this paper is to assess how building sustainability is understood in building research and building practice. The research approach is to review how building researchers and building companies have interpreted sustainability in leading articles and in leading sustainability reports. These are assessed by studying how sustainability is described and then in more detail applying two maturity matrices on the articles and the reports. The preliminary results indicate that there could be a major problem in understanding sustainability among both building researchers and building company managers, which could constitute a significant obstacle to improving building sustainability. This might not only be related to building sustainability but could be a general problem.
Keywords: building value chain; defining building sustainability; measuring building sustainability; sustainable construction; understanding building sustainability